Peningkatan Pemahaman Pasien Rawat Jalan Mengenai Pengelolaan Obat DAGUSIBU (Dapatkan, Gunakan, Simpan, Buang) di Rumah Sakit Umum Daerah Ciamis - Indriastuti, Marlina; Kurniasih, Nia; Harun, Nurhidayati; Ramdhan, Susan Sintia; Silvi Putri Pratama (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Proper medication management is a crucial step in ensuring patient safety and enhancing the efficiency of healthcare services, especially in hospitals. Education on medication management using the DAGUSIBU method (Get, Use, Store, and Dispose) serves as an educational approach to improve the understanding and compliance of healthcare workers and the community. Objective: To improve public understanding of how to use drugs safely and appropriately. Method: The method used was conducted by a pre-test and post-test design involving participants from healthcare workers and pharmacy staff at Ciamis Regional General Hospital. The education was delivered using presentation media and leaflet. Understanding was measured using a questionnaire consisting of multiple-choice questions. Result: These results indicate that the majority of respondents 60% have a good understanding of the material measured in the questionnaire. However, there are around 40% of respondents (categories Sufficient and Less) who show an understanding that still needs to be improved, which could be a concern for further improvement. Conclusion: It is hoped that through this program, the community can implement the DAGUSIBU principle in everyday life to create a healthier and safer environment.